An evaluation of farmer field school training on the livelihoods of cocoa farmers in Atwima District, Ashanti Region, Ghana - Gockowski, J.; Asamoah, C.; David, S.; Nkamleu, G.B.; Gyamfi, I.; Agordorku, S.; Kuti, M.A. (2006)
This report presents findings on the effects of STCP farmer field school training conducted in 2003 with the cocoa farmers of Atwima District of the Ashanti region, Ghana. The focus of the study is on the measurement of changes in behavior with respect to crop husbandry and input usage and the impact on production. The study also measures changes in the participation of children in hazardous tasks which may have occurred as a result of FFS sensitization exercises. The intended utility of this study is to contribute to the further refinement and adaptation of the farmer field school extension approach as applied to the cocoa farming systems of West Africa. The International Institute of Tropical Agriculture (IITA) and CABI organized and conducted the first FFS training and curriculum development workshop for master trainers in March 2003. At this workshop, in addition to the training of master trainers and the development of country action plans, the core elements of the farmer field school curriculum were developed. Researchers from the Cocoa Research Institute of Ghana (CRIG) and other national institutes provided the scientific backstopping underlying the curriculum targeting the integrated management of the cocoa cropping system to ensure sustainable and socially responsible production. There is a strong curriculum focus on the control of black pod disease but attention is also given to the problem of capsids, post harvest techniques, and the social issues surrounding child labor (which are addressed with the collaboration and participation of theWest African Cocoa and Commercial Agriculture Project (WACAP ) of the ILO). One of the problems in developing a regional FFS curriculum for adult education lies in the location-specific and region-specific nature of cocoa agronomic constraints. A much lowerincidence of black pod disease faces Ivorian and Ghanaian cocoa farmers as compared to Cameroon and Nigeria, where the more virulent form of the disease exists and the majority of farmers treat with agro-chemicals. As such, the initial Ghanaian training of trainers also included soil fertility management, mistletoe management, cocoa tree thinning, and postharvest issues deemed to be important for Ghanaian cocoa farmers. Following 3 1/2 weeks of training on the curriculum, the facilitators were ready to begin the farmer field school. The program was initiated with 30 schools and 30 facilitators in the Atwima district of Ashanti region in the first year. In 2003 the average number of participants per school was 28. Farmer training occurred on a biweekly basis with the total number of sessions per school ranging from 11 to 15. On average, the session would last four hours. Working in groups, farmers would observe and discuss dynamics of the cocoa’s ecosystem and the crop development. Simple experimentation protocols such as the black pod disease zoo helped farmers improve their understanding of ecological functional relationships such as the impact of humidity on disease development. To achieve the study objectives, a survey was conducted in February 2005 with a random sample of 225 of the 829 farmers trained in 2003 and a control group sample of 165 cocoa farmers who had not participated. All 30 farmer field schools were represented in the sample with the number of participants interviewed per school ranging from five to 21. The fieldresearch was conducted in February 2005 and focused mainly on farmer practice during the 2004 growing season. A proportionate number of control farmers were sampled in each of the 30 communities. The differences noted in management practices and production (after controlling for differential resource endowments) between the two groups are attributed to the new knowledge gained through the discovery learning exercises of the farmer field school. 4 Major findings include: Children, education and cocoa farming · Significant reductions were noted in the hazardous employment of children as a result of FFS sensitization methods. Specifically among the 2,800 Atwima cocoa producers sensitized since 2003 it is estimated that there are now 540 fewer childrenemployed in heavy field transport, 440 fewer children employed in clearing fields with machetes, and 170 fewer children employed in pesticide application. Based on the above results, scaling up FFS to 50,000 producers in the Ashanti region would result in the voluntary removal of 10,500 children from all hazardous labor tasks with a predicted 3,000 fewer children employed in pesticide application, 9,700 fewer children in heavy load transport and 7,900 fewer children in clearing fields with machetes. School enrollment rates were in excess of 90 percent for 6 to 14 year old children.· Among FFS-trained farmers the level of education was positively associated withproduction output.Willingness to pay and knowledge diffusion· A large majority of control group farmers were willing to pay to attend FFS training.· The amount of tuition fee that farmers were willing to pay for attending a 15-sessionFFS training was negatively affected by producer age and positively affected byyears of schooling.· Nearly 9 in 10 trained farmers indicated that they shared information with on average2 other persons.· Knowledge on cocoa pruning, shade management and phyto-sanitary harvesting wasthe most commonly shared.Tree stock endowments· The average productivity of FFS farmers’ tree stock was more than double that of thecontrol group.· Notable increases as a result of FFS interventions were registered in the number ofproducers planting hand pollinated hybrid cocoa seedlings and the area planted tohybrids.· Farmers acquiring their cocoa farms through share-crop labor exchanges (30% ofsample) had substantially lower production.· Two-thirds of all cocoa farms were established within the last 10 years.· Low average yields of 112 kg ha-1 reflect in part the youthful nature of farmers’ treestocks.Crop management and production differences· Increased application of various crop husbandry practices among FFS-trained farmersrelative to control group farmers was noted.· The application of pesticides showed a response 8 times greater than that of thecontrol group.In sum, FFS training and subsequent changes in management practices are estimated to haveresulted in a net production increase of 14% among the 2003 participants. To achieve thisincrease, producers mainly increased their own labor input and indicated hiring more casuallaborers. While the survey was unable to accurately determine the actual change in labor5inputs, the additional labor costs required to achieve this increase are real and should benetted out of the 14% increase in estimated gross revenues.From several different perspectives it is clear that the FFS training received by participantshas had measurable impacts on their productive capacity and on their views towards childlabor. In support of the significant accomplishments already achieved, severalrecommendations can be made to potentially improve the performance and impact of FFStraining.· More attention should be given to address the specific needs of women cocoaproducers and those acquiring their cocoa farms through a share-cropping exchange.A needs assessment with these two groups is recommended as a first step in adaptingthe curriculum.· Given the scarce resources available for training farmers, criteria are needed to selectparticipants so as to maximize expected returns. Age and educational level of theproducer are recommended as discriminating factors.· The positive results seen vis-à-vis child labor participation in hazardous tasks ishighly encouraging and warrants increased efforts at sensitization through the farmerfield school.· Given that the majority of producers were applying insecticides to control capsidsindependent of the government spraying program but with lower use efficiency vis-àvisthe government program, protocols on the safe and rational use of pesticidesrequire more emphasis in the program than they are currently receiving. Additionally,the Ghana program should seek to develop a protocol for the identification and spotspraying of capsid hot spots.· The facilitation provided by the program in the distribution of improved cocoaplanting material substantially increased the area planted to hybrids among participantfarmers. This practice is to be commended and should be augmented with additionalFFS sessions to deal with nursery techniques and planting/replanting options. These sessions should be added on to the school year for those schools where the majority ofproducers are interested.